Ultrasonically assisted electrophoretic deposition of oxidized graphite nanoparticle onto carbon fiber, amending interfacial property of CFRP. (June 2020) - Nandi, Ankush; Das, Subhankar; Halder, Sudipta; Chakraborty, Anirban; Imam, Muhammad A
The performance of fiber-reinforced composites significantly relies on the microstructure and properties of the fiber–matrix interface. Escalating the aspect ratio of the fiber surface by coating with nanoparticles is a proven technique for improving the fiber/matrix adhesion. Subsequently, improved adhesion between epoxy and fiber, which is ascribed due to improved interfacial friction, chemical bonding, and resin toughening would enhance the interfacial strength of such laminated composites. Here, graphite nanoparticles were oxidized, and these charged particles were coated onto the carbon fibers (CFs) surface using ultrasonically assisted direct current electrophoretic deposition. Functionalization of the graphite nanoparticle upon oxidation was confirmed through dispersion analysis, Fourier transformed infrared spectroscope, thermogravimetric analysis, and field emission scanning electron microscope. The CFs fabrics were grafted with different sets of samples prepared by varying voltage and deposition time. The deposition of oxidized graphite nanoparticle over the CFs was authenticated through field emission scanning electron microscope. A transverse fiber bundle test was carried out to assess interfacial strength between CF and epoxy matrix. The transverse fiber bundle test strength is found 113% higher for CF coated with oxidized graphite nanoparticles at 50 V for 5 min compared to that of as-received sized CF composites. Field emission scanning electron microscopy analysis of transverse fiber bundle test fractures samples identified multiple crack propagation zone owing to the presence of graphite nanoparticle on CF.